Madurez psicológica escolar y toma de decisiones académicas en los estudiantes de la básica superior de la Unidad Educativa Combatientes de Tapi - López Hoyos, Sebastián Andrés (2021)
The general objective of this research work is to determine the scholar-psychological maturity and identify the level of academic decision-making in order to carry out an analysis between both study variables in the upper elementary students from the “Combatientes de Tapi” Educative Unit. School psychological maturity and decision-making is a topic that has achieved significant relevance since there is a close relationship between them. It is a problem that has increased notably in a very accelerated way as the years go by, it mainly affects adolescents at a social, family and school level.